Survival characteristics of monophasic Salmonella Typhimurium 4, [5], 12:i:- strains derived from pig feed ingredients and compound feed. (June 2016) - Burns, Anne Marie; Duffy, Geraldine; Walsh, Des; Tiwari, Brijesh K.; Grant, Jim; Lawlor, Peadar G.; Gardiner, Gillian E.
Abstract: The presence of Salmonella in animal feed or feed ingredients at the feed mill or on-farm is a cause for concern, as it can be transmitted to food-producing animals and subsequently to humans. The objective of this study was to determine the survival characteristics of five feed ingredient- and feed-derived monophasic Salmonella Typhimurium 4, [5], 12:i:- strains. The first part of the study investigated thermal inactivation using an immersed heating coil apparatus. A Weibull model provided a good fit, with low RMSE values (0.04–0.43) and high R 2 values (0.93–0.99) obtained. There was considerable inter-strain variation in heat resistance, with D-values ranging from 397.83 to 689 s at 55 °C, 11.35–260.95 s at 60 °C and 1.12 to 6.81 at 65 °C. Likewise, z-values ranged from 2.95 to 5.44 °C. One strain demonstrated a significantly higher thermal tolerance, even though it had been isolated from a meal feed. However, overall the strains investigated do not appear to be that much more heat resistant than Salmonella previously studied. The second part of this study involved assessing the ability of the five Salmonella strains to survive during storage over a 28-day period in pelleted weaner pig feed treated with 0.3% sodium butyrate. While a mean reduction in the Salmonella count of 0.79 log10  CFU was seen in the treated feed during the storage period, a reduction (albeit only 0.49 log10  CFU) was also observed in the control feed. Although there was no overall effect of treatment, sodium butyrate resulted in reductions in Salmonella counts of 0.75 and 0.22 log10  CFU at days 14 and 24 of feed storage, respectively but at the end of the 28-day storage period counts were 0.25 log10  CFU higher in the treated feed. Therefore, the sodium butyrate used appears unsuitable as an agent for feed treatment perhaps due to the protective coating on the particular feed additive used. Overall, the results of this study enhance knowledge about the behaviour and survival characteristics of monophasic S. Typhimurium 4, [5], 12:i:- strains in animal feed and may assist the feed industry and pig producers in implementing effective intervention strategies for their control. Highlights: Survival of Salmonella Typhimurium 4, [5], 12:i:- strains was examined. Weibull model was a good fit for thermal inactivation data. There was considerable inter-strain variation in D- and z-values. Sodium butyrate had negligible effects on Salmonella counts in stored feed.